The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/00131946.2016.1231681
|View full text |Cite
|
Sign up to set email alerts
|

“They Think I Am a Pervert:” A Qualitative Analysis of Lesbian and Gay Teachers' Experiences With Stress at School

Abstract: Consensual Qualitative Research was used to develop a framework for understanding the demands faced by lesbian and gay (LG) teachers as a function of the interaction between sexual identity and professional context, including resources used in combatting those demands. Data sources included two interviews each with 11 teachers who each identified as lesbian or gay. Overall, the participants identified a far greater diversity of demands than resources/coping strategies. This speaks to the main finding, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Whether an LGBT teacher decides to come out or remain silent may have an important impact on their career and promotional opportunities. Lineback et al (2016) found that the teachers in their study tried to remain as invisible as possible so as to not draw attention to themselves, acknowledging that this strategy was not conducive to job promotion. Fahie (2016) too found that participants in his study avoided opportunities for promotion, as to do so would 'increase their professional profile and raise their level of visibility within the local community' (p. 402).…”
Section: Introductionmentioning
confidence: 96%
“…Whether an LGBT teacher decides to come out or remain silent may have an important impact on their career and promotional opportunities. Lineback et al (2016) found that the teachers in their study tried to remain as invisible as possible so as to not draw attention to themselves, acknowledging that this strategy was not conducive to job promotion. Fahie (2016) too found that participants in his study avoided opportunities for promotion, as to do so would 'increase their professional profile and raise their level of visibility within the local community' (p. 402).…”
Section: Introductionmentioning
confidence: 96%
“…The recognition of same-sex relationships in the United States has increased, though many individuals with LGBTQ+ identities continue to face discrimination (Lineback et al, 2016). Despite this societal tolerance, research has demonstrated that some schools in the US provide discriminatory environments for lesbian and gay individuals and that teaching is one of the most homophobic professions in parts of the US (DeLeon and Brunner, 2013;Lineback et al, 2016).…”
Section: The International Contextmentioning
confidence: 99%
“…The recognition of same-sex relationships in the United States has increased, though many individuals with LGBTQ+ identities continue to face discrimination (Lineback et al, 2016). Despite this societal tolerance, research has demonstrated that some schools in the US provide discriminatory environments for lesbian and gay individuals and that teaching is one of the most homophobic professions in parts of the US (DeLeon and Brunner, 2013;Lineback et al, 2016). According to DeLeon and Brunner (2013), attempts have even been made to exclude LGBTQ+ teachers from the profession to lessen the risks of sexual abuse, pedophilia, molestation, and the recruitment of children into queer lifestyles (Jackson, 2007;Mayo, 2008;Lineback et al, 2016).…”
Section: The International Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…These stressful interactions can then lead to psychological, behavioural, and physical problems. For example, stress at work for sexual minority employees has been linked to burnout, self‐stigmatization, fear of discrimination, and work‐family conflict (e.g., Lineback, Allender, Gaines, McCarthy, & Butler, ; Rostosky & Riggle, ; Sawyer, Thoroughgood, & Ladge, ).…”
Section: Introductionmentioning
confidence: 99%